2022
DOI: 10.3389/fimmu.2022.964274
|View full text |Cite
|
Sign up to set email alerts
|

Combined – whole blood and skin fibroblasts- transcriptomic analysis in Psoriatic Arthritis reveals molecular signatures of activity, resistance and early response to treatment

Abstract: BackgroundAn interplay between immune cells and resident skin and joint stromal cells is implicated in psoriatic arthritis (PsA), yet the mechanisms remain elusive with a paucity of molecular biomarkers for activity and response. Combined transcriptomic and immunophenotypic analysis of whole blood and skin fibroblasts could provide further insights.MethodsWhole blood RNA-seq was performed longitudinally in 30 subjects with PsA at the beginning, one and six months after treatment, with response defined at six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…study of PBMCs derived from PsA patients vs healthy controls showed a positive enrichment in PsA of several terms related to inflammation such as 'inflammatory response', 'TNFa signaling via NFkB', 'complement', 'IL2 signaling', and 'IFNa and IFNg response' (49) consistent with our results. Interestingly, longitudinal assessment of PBMC transcriptome revealed that transcriptomic alterations as soon as 1 month after treatment initiation could predict response at 6 months, with responders showing early downregulation of the proinflammatory gene signatures (49).…”
Section: Discussionmentioning
confidence: 99%
“…study of PBMCs derived from PsA patients vs healthy controls showed a positive enrichment in PsA of several terms related to inflammation such as 'inflammatory response', 'TNFa signaling via NFkB', 'complement', 'IL2 signaling', and 'IFNa and IFNg response' (49) consistent with our results. Interestingly, longitudinal assessment of PBMC transcriptome revealed that transcriptomic alterations as soon as 1 month after treatment initiation could predict response at 6 months, with responders showing early downregulation of the proinflammatory gene signatures (49).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the expression of PD-1 and its ligands PD-L1 and PD-L2 showed a stepwise increase early in disease progression to RA, however, histological examination of synovial tissue biopsies showed very low levels of PD-L1 possibly due to epitope masking mediated by the increased levels of soluble PD-1 in the serum of patients with RA [50] . In addition to the identification of signalling pathway enrichment in RA synovial inflammation during different stages of disease, the potential identification of PsA specific transcriptomic signature in the blood could facilitate diagnostic biomarker discovery [51] .…”
Section: Limitations Of Histological Evaluation Of Synovial Pathologymentioning
confidence: 99%
“…In a recently published observational study including 30 PsA patients, similar pathways including inflammatory response, complement, IFNα and IFNγ response, oxidative phosphorylation, adipogenesis, fatty acid metabolism, EMT, angiogenesis and signalling cascades related to WNTβ catenin and TGFβ where identified. 14 Another observational study of 60 patients also identified inflammation, immune response, apoptosis, cell cycle regulation and proliferation, cell migration and invasion, extracellular matrix remodelling, bone remodelling, angiogenesis, signal transduction as important pathways reflected in the peripheral blood cells of PsA patients. 15 Thus, our results provide insights to biomarkers and pathways driving disease activity in PsA and highlights the importance of IL6-JAK-STAT3 signalling.…”
Section: Psoriatic Arthritismentioning
confidence: 99%